Motor Competency of Orang Asli Children from the Royal Belum Rainforest Reserves - Harun, Hafizah; Haron, Habibah Norehan; Ibrahim, Halijah; Kamaruddin, Azlina; Rahman, Rozana Abd (International Journal of Economics and Financial Issues, 2015)
Physical inactivity is a growing problem among children of today’s society. Whereas levels of physical activity are influenced by motor competence, defined as the ability to execute different motor tasks necessary to manage everyday life and reduce probability of other health risks (over and under nutrition). These skills are developed early in childhood, which can be categorized as fundamental motor skills (FMS), however its acquisition has mostly assessed European children. Normative data on Asian or Malaysian sample are scarce and indigenous or Orang Asli children nonexistent. The main aim of this study was to investigate FMS in the object control skill category among Orang Asli children in the Royal Belum (RB) Forest Reserves of Gerik Perak. All the seven year-olds children (n=28) from two primary schools of Royal Belum participated in the study. Anthropometry of the children was collected prior to the FMS assessment. Children from Sekolah Kebangsaan Banun (n=10) were 5% taller and 21% heavier and their BMI ratios 9% higher than children from SK Tiang (n=18). However, these children were lower than normative height (below -2 SD) and weight (-1 SD) of W.H.O data. FMS scores indicated that 55% more children from SK Tiang (an inner village) have higher scores than children from SK Banun (40%) in the administered test. Differences in the levels of FMS development are influenced by many factors that include the environment, socioeconomic status, parental influences and structured physical education in schools. The result was based on only one test protocol; there is a battery of tests that may have different outcomes. Nevertheless these initial findings may provide guideline for early identification of disparity between children and provide information to the responsible authorities (schools, JHEO, researchers) to support development of motor competence and lifestyle practices among young children in the community. Keywords: Physical Activity, Motor Competence, FMS - Fundamental Motor Skills, Object Control Skill JEL Classifications: R00